Long‐term outcome of obstetric anal sphincter injury repaired by experienced obstetricians. Issue 2 (10th May 2014) - Salim, Raed; Peretz, Hadar; Molnar, Robert; Braverman, Meirav; Hatokay, Aliza; Shalev, Eliezer
Abstract: Objective: To examine the long‐term outcomes of women with obstetric anal sphincter injury (OASI) repaired by obstetricians without the involvement of colorectal surgeons. Methods: A retrospective cohort study was undertaken of women who had been admitted for delivery between 2004 and 2012. All OASIs had been repaired by experienced obstetricians using the end‐to‐end technique. An unexposed group (no OASI) was matched at a ratio of 1:1. Fecal incontinence was graded using a modified Wexner questionnaire. Results: Overall, 113 OASIs were recorded. Sixty‐seven (59.3%) and 71 (62.8%) women from the exposed and unexposed groups, respectively, agreed to participate in the study ( P = 0.9). Continence to both stool and gas was reported by 48 (71.6%) and 64 (90.1%) women in the exposed and unexposed groups, respectively ( P = 0.03). The incidence of urgency, dyspareunia, and use of a pad or constipating agents was the same in both groups. Conclusion: The long‐term outcome of OASI repair performed by experienced obstetricians is comparable to that reported in the literature. Some women who did not sustain an OASI reported fecal incontinence, which suggests that only a proportion of fecal incontinence can be attributed to OASI.